Palladium-Catalyzed Oxidative Arylalkylation of Unactivated Alkenes: Dual C–H Bond Cleavage of Anilines and Acetonitrile - Zhang, Hao; Chen, Pinhong; Liu, Guosheng (Synlett, 2012)
A palladium-catalyzed oxidative arylalkylation of unactivated alkenes involving dual C–H bond cleavage of arene and acetonitrile was developed. This reaction was promoted by pyridine as a ligand, and the ratio of palladium to pyridine is vital for this transformation. A series of nitrile-containing indolines were efficiently provided in moderate to good yields.
Keywords: palladium; C–H activation; alkenes; acetonitrile; pyridine